Investigating the Use of First Language in English Language Teaching at secondary School - Suardi Sahid; Riana Murianty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Papuan Malay is the second language considered by Papuans after the regional language and not a few people use Papuan Malay in various aspects of life, one of which is in the field of education. At present, there are many phenomena of using Papuan Malay as the language used in mastering English. This study applied a qualitative descriptive method with six English teachers in secondary schools as research subjects. The data collected through classroom observation and depth interviews. The finding obtained that Papuan Malay is used in presenting instructions, providing motivation and explanations in teaching materials. The finding also revealed that the teacher used the first language to show anger, sadness, and happiness, its use is carried out with the aim of providing a sense of comfort when communicating and interacting properly between the teacher and students.